Manifestation of University Lecturers' Competences of Emotional Intelligence - Rudaitienė, Loreta (Acta Paedagogica Vilnensia, 2004)
The goal of the paper is to investigate the characteristics of lecturers’ emotional competences in academic communication with their students and to define the areas that yield the lowest EIC scores. After presenting the main notions of emotional intelligence and contemplating the relationship between emotional intelligence (Salovej and Mayer 1990, 1997; Mayer, Salovej and Caruso 2000) and emotional competence (Goleman 1998; 2001), the research methodology is based on Goleman (2001) emotional competencies as (EI)-based theory of performance and Jacob's (2001) algorithm of teacher's emotional intelligence competencies. The key competencies of lecturers’ emotional intelligence include: influence, developing others, empathy, service orientation, self-control accurate self-assessment, self-confidence, teamwork, collaboration and conflict management. The sample was randomly selected from 92 third-year students. They were interviewed by an anonymous questionnaire of closed questions. The research data shows general tendencies and on average the scores are not high. According to students, lecturers’ emotional competences of self-confidence and empathy suggest the lowest scores. This leads to the assumption this low data scores might have influenced low results of lecturers’ the emotional competences of service orientation, developing others and i11flue11ce. Relatively higher scores in self-control and conflict management may cause concern about the consequences of such lecturers’' behaviour suppression with regard to low scores of self-confidence and empathy. The research data shows that the emotional competences of teamwork and collaboration show relatively higher results; however, again, the perspective of creating synergy in these activities is doubtful if one considers low scores in empathy and service orientation. The difference in scores between self-assessment and self-confidence shows that no matter whether lecturers know their strengths and weaknesses, they very often tend to devalue themselves and kill feelings of self-pride. In conclusion, lecturers' emotional competence of influence demonstrates its relatively superficial level, mainly manifesting itself in well-preserved etiquette. In conclusion we should stress out that, first, the research challenges lecturers’ re-evaluation of their new roles as educators by expanding their vision on the task of education and by appreciating the significance of self-development of emotional intelligence; second, the received results show that the development of emotional intelligence as an ability to recognize emotions and their meaning and to use them in assisting reflection as well as an ability to develop personality characteristics by solving emotional problems empathically is the basis for developing ethically-true emotional competences.
Keywords: higher education; university lecturer; competences; emotional intelligence